2020
DOI: 10.1111/apa.15606
|View full text |Cite
|
Sign up to set email alerts
|

Parents' perspectives, information needs and healthcare preferences when consulting for their children with bronchiolitis: A qualitative study

Abstract: Aim Bronchiolitis is the leading cause of hospitalisation in infants, but parental experiences have not been well described. This study explored parents’ experiences and asked them how they wanted to receive information. Methods A qualitative study was conducted in a tertiary paediatric hospital in Québec, Canada. It consisted of semi‐structured interviews with 15 parents of 13 children with bronchiolitis. The interview guide was constructed by a multidisciplinary team that included a parent. The interviews, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Prior to the implementation of the project, knowledge about bronchiolitis was limited across all stakeholder groups (apart from the Core Team) and many stakeholders had either not heard of bronchiolitis or information was not contemporary. As seen in other studies, parents wanted information about bronchiolitis, including knowledge of what to look for and how to interpret the severity of symptoms [ 15 , 17 ] and knowing what actions to take when they became aware of symptoms and signs of bronchiolitis. Lack of knowledge about bronchiolitis has been shown to contribute to parental anxiety when their child has bronchiolitis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to the implementation of the project, knowledge about bronchiolitis was limited across all stakeholder groups (apart from the Core Team) and many stakeholders had either not heard of bronchiolitis or information was not contemporary. As seen in other studies, parents wanted information about bronchiolitis, including knowledge of what to look for and how to interpret the severity of symptoms [ 15 , 17 ] and knowing what actions to take when they became aware of symptoms and signs of bronchiolitis. Lack of knowledge about bronchiolitis has been shown to contribute to parental anxiety when their child has bronchiolitis [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…As seen in other studies, parents wanted information about bronchiolitis, including knowledge of what to look for and how to interpret the severity of symptoms [ 15 , 17 ] and knowing what actions to take when they became aware of symptoms and signs of bronchiolitis. Lack of knowledge about bronchiolitis has been shown to contribute to parental anxiety when their child has bronchiolitis [ 17 ]. A systematic review reported that most information is oriented to parents whose child has been hospitalised with limited information focused on parents caring for their child at home [ 16 ]; this is clearly a gap that the PCC project was trying to address.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They report that four of the five models showed superior performance to logistic regression. Piché‐Renaud et al 9 studied the experiences of parents of children with bronchiolitis in a hospital in Quebec and concluded that parental knowledge was low and that standardised educational tools were useful, but insufficient. Meanwhile, Korppi et al 10 report that Interleukin‐1 receptor‐associated kinase‐4
gene variations may increase post‐bronchiolitis asthma risks.…”
Section: Exploring Hospital Stays For Acute Bronchiolitis Parental Knowledge and Genetic Variationsmentioning
confidence: 99%
“…spectives, information needs and healthcare preferences when consulting for their children with bronchiolitis: A qualitative study'. 2 We want to express our thanks to Perry and Singh for their interest in our article.…”
mentioning
confidence: 97%